Effects of Consumer Search Behavior Typology on the Relationship Between Customer Satisfaction and Behavioral Intentions - Wahyuningsih, Wahyuningsih (The South East Asian Journal of Management, 2007)
The author investigates how consumer search behavior typology affects the relationship between customer satisfaction and behavioral intentions. The results show that the type of consumer as defined by whether and how they search for information (passive, rational-active, relational-dependent) perceive different levels of satisfaction and performs differently on satisfaction-behavioral intentions linkages. Relational-dependent and rational-active consumers are found to perceive higher satisfaction levels, and to express stronger intentions to engage in positive behavioral intentions than passive consumers. The identification of satisfaction and behavioral intentions within each search type allows managers to satisfy their consumers; hence, the company will obtain higher profit.